Association between First-Generation Antihistamine Use in Children and Cardiac Arrhythmia and Ischemic Heart Disease: A Case-Crossover Study - Ju Hee Kim; Hye Ryeong Cha; Eun Kyo Ha; Ji Hee Kwak; Hakjun Kim; Jeewon Shin; Hye Mi Jee; Man Yong Han (MDPI AG, 2023)
Cardiotoxicity from first-generation H1-antihistamines has been debated since the 1990s. However, large-scale studies on this topic in a general pediatric population are lacking. This study aimed to assess the association between first-generation H1-antihistamine use and cardiovascular events in a nationwide pediatric population. In this case-crossover study, the main cohort included children with cardiovascular events from the National Health Insurance Service database (2008-2012 births in Korea) until 2018. The second cohort excluded children with specific birth histories or underlying cardiovascular diseases from the main cohort. Cardiovascular events of interest included cardiac arrhythmia and ischemic heart disease. Odds ratios (ORs) of cardiovascular events were estimated using conditional logistic regression models, comparing first-generation H1-antihistamine use during 0-15 days before cardiovascular events (hazard period) with use during 45-60 and 75-90 days before events (control periods). Among the participants, 1194 (59.9%) were aged 24 months to 6 years, and 1010 (50.7%) were male. Cardiovascular event risk was increased among users of first-generation H1-antihistamines (adjusted OR [aOR], 1.201; 95% confidence interval, 1.13-1.27). Significant odds of cardiovascular events persisted within 10 and 5 days (aOR, 1.25 and 1.25). In the second cohort, the association was comparable with that in the main cohort. Our findings indicate that cardiovascular event risk is increased in children who are administered first-generation H1-antihistamines.